Pockets of promise: exploring innovation and complexity of remote ECEC service delivery in Australia - Adamson, Elizabeth; Skattebol, Jennifer (Frontiers in Education, 2023)
Introduction The existing funding architectures for early childhood education and care (ECEC) services in Australia are incompatible with the needs of remote and First Nations communities. The system relies on a market-based model for ECEC where funding flows to users to choose what service to use. This model is not viable or sustainable in remote and Aboriginal communities. In this paper, we ask what we can learn from alternative models of ECEC that serve remote, largely Indigenous communities. Methods This research is based on interviews with 10 key stakeholders. Potential participants were identified using three selection criteria – advocacy roles and experience in ECEC services in remote locations (evident in relevant parliamentary reviews and inquiries), depth of knowledge about First Nations perspectives about ECEC models, and broad understandings of the Australian ECEC system. Three themes were explored: funding context; Quality and regulatory context and Future research. The study design was underpinned by critical policy approaches that advocate for collaboration and coordination among researchers and stakeholders in order to address complex problems. Results Analysis of the interviews illuminated the complex structural and cultural elements shaping the design of, and access to, ECEC in remote communities. Stakeholders argued that the ECEC system should be universal in that it delivers young children the services they need and that this requires the development of a definition of ‘universality’ that enables communities to define their own ECEC needs and the types of services best suited to them. The importance of community-led design and delivery highlighted the need to align structural and cultural aspects of quality standards and address workforce needs. There is an urgent need for deeper consultation with First Nations organisations to better understand community-specific needs and solutions. Discussion The paper outlines the complexities and nuances of ECEC service delivery in remote communities. It is intended to foster discussion about current initiatives, challenges, and futures possibilities for ECEC in remote communities in Australia. These findings concur with other research that indicates a need for community led service delivery and design calls for stronger equity-based partnerships between First Nations and non-First Nations researchers and organisations.